Do carbon emissions affect the cost of capital? Primary versus secondary corporate bond markets - Kim, Daniel; Pouget, Sébastien (Journal of Corporate Finance, 2026)
We empirically study whether carbon emissions affect firms’ cost of capital raised on conventional bond markets. We find that firms with higher carbon emissions face higher spreads in the secondary market but not in the primary market. We show that this gap is related to uncertainty about climate concerns that affects differently primary and secondary market. This gap is also affected by the reputation of underwriting dealers: high reputation promotes the incorporation of climate concerns into bond yields. Our findings imply that, on average, carbon emissions do not affect the cost of capital in bond markets, thereby reducing firms’ financial incentives for decarbonization.